FARS ANALYSIS ON NATIVE WRITER’S AND ESL WRITER’S ACADEMIC ARTICLE - Nuraini (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
This Paper is used to apply the FARS (Framework for Analysis of the Relational Structure) model of discourse analysis. In this paper, the writer tries to analyze the in the text in order to recognize the relation between segment and find the plausibility of the application of FARS relation to the writer’s massage which is attemted to communicate in the global level of the text and how it is developed in lower level or in micro level of the text. This analisis is attampeted to show the prominence of paratactic and hypotatic relation may relates to writer massage which is delivered within the text. It is also used to present the comparison of applicability of CARS and FARS analysis in language pedagogy. FARS analysis is focused on the study of discourse structure, textual coherence and fungtional of textual relation. FARS analysis is developed based on the RST (Rhetoritical Structure Theory) model of discourse analysis. The three main claims found in RST are abuot the predominance of nucleus/ Satellite structural pattern, the functional basis of hierarchy, and the communicative role of structure (Mann & Thompson, 1988). However, in FARS these three main points are presented a little bit different in the number of relation, the taxis principles of each relations and the name of the relation. Abstrak Pada tulisan analisa diskursus FARS digunakan untuk menganalisa teks guna mengetahui hubungan antar segment pada tulisan ESL dan Native Writer . Selain itu analisa in juga untuk menemukan tingkat kelogisan dari aplikasi FARS terhadap pesan yang ingin dikomunikasikan oleh penulis pada tingkat global dari teks yang dianalisa dan tingkat kelogisan ini dibangun pada level yang lebih rendah atau pada level mikro. Artikel ini mencoba menunjukkan relasi parataksis dan hipotaksis yang menonjol yang berhubungan dengan pesan penulis yang disampaikannya melalui teks. Artikel ini juga untuk menunjukkan perbandingan pengaplikasian analisa CARS dan FARS pada pengajaran bahasa. Analisa FARS adalah studi stuktur diskursus , tekstual koherensi, dan fungsi relasi tekstual. Analisa ini dikembangkan berdasarkan model analisa RST (Rhetoriticl Structure Theory). Tiga klaim pada RST adalah tentang keunggulan inti/ pola strukstural satelit, tingkatan dari dasar fungsi, dan peran komunikatif dari struktur tulisan. Namun demikian, pada analisa FARS, tiga poin inti ini disajikan sedikit berbeda pada jumlah relasi, prinsip taksis pada tiap- tiap relasi dan penamaan relasinya.